PP.27.12: RESISTANT HYPERTENSION IS ASSOCIATED WITH MORE PRONOUNCED STRUCTURAL ALTERATIONS OF SUBCUTANEOUS SMALL RESISTANCE ARTERIES. (June 2015) - Rosei, C. Agabiti; De Ciuceis, C.; Rossini, C.; Muiesan, M.L.; Salvetti, M.; La Boria, E.; Sarker, A.; Porteri, E.; Gavazzi, A.; Paini, A.; Petroboni, B.; Pileri, P.; et al.
Abstract : Objective: It is was suggested that, in resistant hypertension, the presence of particularly pronounced microvascular alterations may contribute to explain the relative lack of response to treatment. Similarly, in diabetic patients, the persistence of an altered microvasciular structure, despite the administration of multiple drug combination treatment, might partly explain the difficulty to reach target blood pressure values, especially for systolic blood pressure. Figure. No caption available. Design and method: For this reason, we investigated a population of 94 treated essential hypertensive patients. Secondary forms of hypertension were excluded according to standard clinical evalutions and biochemical or instrumental assessment, and in all patients a 24-hour blood pressure monitoring was performed in order to exclude a white coat effect. In all patients, we evaluated small resistance arteries morphology by a wire micromyographic approach (Mulvany's technique). A small amount of subcutaneous tissue was obtained by local biopsy or during election surgery and subcutaneous small resistance arteries were dissected and mounted on a myograph; the media to lumen ratio (M/L) was then measured. We subdived our patents according to the presence or not of resistant hypertension (clinic blood pressure values above 140/90 mm Hg despite administration of three antihypertensive agent including a diuretic and 24-hour blood pressure values > 130/80 mm Hg). Sixteen patients had true resistant hypertension, and were compared with the remaining 78 patients with non-resistant hypertension. Results: Results are summarized in the Table (**p < 0.01, ***p < 0.001 vs. non resistant hypertensive patients). The two groups were also different in terms of mean age (57 ± 12 vs. 67 ± 7 years, p = 0.016 and pulse pressure/stroke volume, a rough index of large artery distensibility: 0.63 ± 0.31 vs. 0.90 ± 0.33, p = 0.02). Conclusions: Our data suggest that hypertensive patients with true resistant hypertension have greater microvascular structural alterations compared with non-resistant hypertensive patients. This could explain, at least in part, the resistance to pharmacological treatment and the high cardiovascular risk observed in these patients.